Pengaruh Sektor Pariwisata Terhadap Tingkat Kemiskinan Kabupaten/Kota Di DIY Pasca Pembangunan Yogyakarta International Airport, 2016-2021 - Elisabeth Putri Lucitania; Astuti Rahayu (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
Recently through various social media, there has been an increase in the level of poverty in Indonesia, especially in the Province of Daerah Istimewa Yogyakarta (DIY). This study aims to find out how the influence of the tourism sector, which consist of the variables Original Local Government Revenue, Gross Regional Domestic Product, and Labor on Poverty levels in Indonesia after the construction of Yogyakarta International Airport (YIA). The type of research used is descriptive quantitative. The data used is in the form of secondary data obtained through the publication of The Central Statistic Agency and The Tourism Statistic Book, which includes data on tourism sector. The analytical tool used in this study is panel data regression, which is a combination of time series data for 2016-2021 and cross section data in 5 Regencies in the DIY Province. The results of this study indicate that the Original Local Government Revenue and the YIA post-development dummy variable have no effect on the Poverty level, while the GDP and Labor variables have negative effect on the poverty rate in DIY.